2018
DOI: 10.3390/genes9010018
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-Specific Mis-Splicing and Heart Disease Exemplified by RBM20

Abstract: Alternative splicing is an essential post-transcriptional process to generate multiple functional RNAs or proteins from a single transcript. Progress in RNA biology has led to a better understanding of muscle-specific RNA splicing in heart disease. The recent discovery of the muscle-specific splicing factor RNA-binding motif 20 (RBM20) not only provided great insights into the general alternative splicing mechanism but also demonstrated molecular mechanism of how this splicing factor is associated with dilated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 77 publications
0
30
0
1
Order By: Relevance
“…Splicing regulation of RBM20 in TTN splicing has been validated only in TTN middle Ig and PEVK region (Guo et al, 2012; 2013; Li et al, 2012; 2013; Rexiati et al, 2018). It is unknown whether RBM20 also regulates the Z-band and M-band TTN splicing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Splicing regulation of RBM20 in TTN splicing has been validated only in TTN middle Ig and PEVK region (Guo et al, 2012; 2013; Li et al, 2012; 2013; Rexiati et al, 2018). It is unknown whether RBM20 also regulates the Z-band and M-band TTN splicing.…”
Section: Resultsmentioning
confidence: 99%
“…These isoforms are mainly generated from alternative splicing of the I-band exons encoding the middle immunoglobulin (Ig) region and PEVK (proline (P), glutamate (E), valine (V), and lysine (K) residues) region (Zhu et al, 2017; Greaser et al, 2008; Guo et al, 2012; 2013; Li et al, 2012; 2013). The major splicing pathways in the middle Ig domain have been well characterized (Zhu et al, 2017; Rexiati et al, 2018). Recently, a splicing factor called RNA binding motif 20 (RBM20) has been identified that regulates TTN middle Ig exon splicing (Guo et al, 2012; Li et al, 2013; Methawasin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…В 2009г RBM20 был впервые описан в качестве гена, связанного с развитием ДКМП [8,11,[14][15][16][17][18]. Позже было показано, что патогенные варианты этого гена связаны с развитием 2-3% случаев ДКМП во всех возрастных группах [14,15].…”
Section: Discussionunclassified
“…Consequently, transcribed regions of interest, which are shorter than 25 nucleotides, for example some of the short exons, are not targeted. This is an important limitation in the context of DM1, as some AS events previously described in DM1, such as AS of exon 5 in cardiac troponin T (TNNT2) [22] cannot be detected. Each continuous section of DNA can be targeted by a collection of up to four probes, referred to as probeset.…”
Section: Affymetrix Genechip™ Human Exon 10 St Microarraymentioning
confidence: 99%